Leadership Politics and the Evolution of the Universal Health Insurance Reform in Peru - Midori de Habich (Taylor & Francis Group, 2019)
Peru is now on a path toward achieving universal health coverage (UHC), with 87% of its population covered by health insurance. This paper describes the politics surrounding the agenda setting and policy formulation process that led up to the adoption of Peru's Universal Health Coverage Act in 2009, which has been instrumental in expanding coverage. This reform established a mandatory health insurance system, which includes an Essential Health Benefit Package (Plan Esencial de Aseguramiento en Salud-PEAS) that is financed by three health insurance schemes (subsidized, contributory and semi-contributory). Collectively these schemes are intended to cover the entire population of Peru. In exploring the politics of the health reform process, the commentary applies the Political Economy of Health Financing Framework, presented in this special issue. It does so from the point of view of a participant in the reform process. Some broader lessons emerge that extend beyond Peru regarding the changing nature of the leadership roles in each phase of the policy cycle. In particular, the analysis highlights the importance of a consensus building process across a range of political stakeholders to set the health reform on the policy agenda and as well as to preemptively identify and resolve disagreements that might arise in the legislative phase.